2009
DOI: 10.2174/092986709788186165
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into PPARγ Ligands Binding

Abstract: Peroxisome Proliferator Activated Receptors (PPARs) are a family of three related nuclear receptors first cloned in 1990. Their involvement in glucidic and lipidic homeostasis quickly made them an attractive target for the treatment of metabolic syndrome, the most prevalent mortality factor in developed countries. They therefore attracted much synthetic efforts, more particularly PPARgamma. Supported by a large number of crystallographic studies, data derived from these compounds lead to a fairly clear view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 74 publications
1
44
0
2
Order By: Relevance
“…DNA fragmentation assay was carried out treating HT-29 cells with 20 lM cladosporol A and, simultaneously, with 5 lM cladosporol B for different times (12,24,48 and 72 h). After treatment, the cells were harvested and washed with 1 ml of PBS, resuspended in 100 ll of PBS.…”
Section: Dna Fragmentation Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…DNA fragmentation assay was carried out treating HT-29 cells with 20 lM cladosporol A and, simultaneously, with 5 lM cladosporol B for different times (12,24,48 and 72 h). After treatment, the cells were harvested and washed with 1 ml of PBS, resuspended in 100 ll of PBS.…”
Section: Dna Fragmentation Assaymentioning
confidence: 99%
“…To investigate whether cladosporol B is endowed with antiproliferative activity as cladosporol A, we assessed the growth of colon carcinoma HT-29 cells treated for different time points (24,48 [7]. To confirm these results, we treated HT-29 cells with increasing concentrations of cladosporol B or A for 8, 24, 48 and 72 h and counted the surviving cells.…”
Section: Cladosporol B Inhibits the Growth Of Human Ht-29 Cell Linementioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of a large number of crystallographic structures of the PPARc ligand-binding domain (LBD) bound to an agonist have revealed that PPARc has at least two binding modes in a single binding site. These two binding modes correspond to full and partial agonists [9]. The binding pocket of PPARc has a Y-shaped form, consisting of an entrance (arm III) that branches off into two pockets.…”
Section: Introductionmentioning
confidence: 99%
“…Arm I is the only substantially polar cavity of the PPARc ligand-binding domain, whereas arms II and III are mainly hydrophobic [10]. Full agonists occupy arm I, making a net of hydrogen bonds with the side chains of Ser289, His323, His449 and Tyr473 [9,11]. These interactions stabilize H12 and are responsible for the transactivation activity of PPARc [9,11].…”
Section: Introductionmentioning
confidence: 99%